Lateral Abdominal Wall Reconstruction - Kapur, Sahil K.; Butler, Charles E. (Seminars in Plastic Surgery, 2018)
Lateral abdominal wall defects, while rare, present a more challenging problem than commonly encountered ventral defects due to the complexity of the anatomy, physiologic forces, and impact of muscle denervation. The lateral abdominal wall encompasses a large surface area ranging from the costal margin superiorly to the iliac crest inferiorly and from the linea semilunaris anteriorly to the paraspinous musculature posteriorly. The ratio of muscle to fascia/aponeurosis is much higher, which makes repair through muscle tissue versus fascia less secure. Furthermore, these defects are subject to asymmetric forces caused by the independent contraction of anterior and posterior muscle units, which lead to unbalanced strain and hernia progression. These features necessitate the use of wide underlay mesh load bearing repairs supported by the static pillars of the abdominal wall. Management can be further complicated when defects extend beyond the defined boundaries, requiring surgical repair to be adapted based on the border structures involved. Primary fascial coaptation may not be as easily accomplished, and therefore careful planning is important to ensure stable coverage of exposed mesh.
Keywords: flank hernia; pillar-anchored repair; bioprosthetic mesh; lateral abdominal wall reconstruction